Magnetic properties of the Ce-Rh binary phases - Kappler, J.P.; Lehmann, P.; Schmerber, G.; Nieva, G.; Sereni, J.G.; Sereni, Julián; Nieva, Gladys (EDP Sciences, 1988)
Fil: Nieva, G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina